Challenges in the popularization of the earth sciences: geotourism as a new medium for the geology dissemination - Garofano, Matteo (Anuário do Instituto de Geociências, 2012)
This article contains some remarks made by the Geotourism Association on common problems found in the development of geotourism. The main issues considered are related to the analysis of the methods used in scientific communication, the problems raised by the use of geological language, the delineation of the geotourists' profile, the functioning of museums. The paper also takes into account Italian data that draw out to considerations about the sustainability of a specific form of tourism, the underground geotourism.